Novel family of fused tricyclic [1, 4]diazepines: Design, synthesis, crystal structures and molecular docking studies. Issue 24 (15th June 2017) - Adamski, Ariel; Kruszka, Dariusz; Dutkiewicz, Zbigniew; Kubicki, Maciej; Gorczyński, Adam; Patroniak, Violetta
Abstract: An efficient one-pot strategy for the synthesis of a new family of imidazo[1, 4]diazepines has been developed and its mechanism has been proposed, which follows a seven-membered ring closure reaction. The condensation of 2- and 4-imidazolecarboxaldehyde with pyrazole amines provides six compounds1–6, which are based on two types of fused tricyclic scaffolds. All presented compounds were fully spectroscopically characterized and their structure was unambiguously determined by single crystal X-ray crystallography. Molecular docking studies reveal a high similarity between binding modes of diazepines1, 6 and eticlopride in the dopamine D3 receptor, as well as between enantiomers2 S, 6 S and nortriptyline in dopamine transporter DAT. Graphical abstract: